STRENGTHENING THE REGULATORY CONCEPT OF NOTARY SUPERVISION BY THE FINANCIAL SERVICES AUTHORITY IN INDONESIA'S CAPITAL MARKET ACTIVITIES - Ismadi, Wahyu; Tumanggor, M. S.; Widjojo, A. G. M. (International Journal of Social Service and Research, 2024)
This study examines the supervision of notaries by the Financial Services Authority in Indonesia's capital market, its implementation, and proposes alternative solutions to strengthen the concept. It provides a comprehensive examination of current supervisory practices, highlighting the effectiveness and challenges of regulatory supervision. The research also proposes alternatives to strengthening the supervisory framework, potentially influencing policy improvements and enhancing governance and integrity of notarial practices.